Do we have Governance in Rural Commodity Value Chains? Evidences from Niger State, Nigeria (Lapai Journal of Economics, 2021)
This study deployed the Value Chain Approach (VCA) to study governance in rural commodity value chains while focusing on yam value added products within Niger State, Nigeria. The question of whether actors within the yam industry respects the food safety standards endorsed by the standardization bodies of the government or not is the major crux in this study. The study deployed qualitative case study methodology and the procedures utilized for data gathering were nine structured interviews, review of past literature and observation using the overt technique. The findings of the study revealed that governance and food safety measures are well spelt out by the certification bodies but what isn’t clear enough is the implementation of food safety measures and governance within the rural settings where many unregistered actors participate in value chains. The findings suggest that disintegration in value chain governance may limit the market exploitability of yam value added products, specifically yam flour, which is mostly traded in the rural markets and this could further make international competitiveness less possible.